2004
DOI: 10.1038/ng1418
|View full text |Cite
|
Sign up to set email alerts
|

Loss of BBS proteins causes anosmia in humans and defects in olfactory cilia structure and function in the mouse

Abstract: Defects in cilia are associated with several human disorders, including Kartagener syndrome 1 , polycystic kidney disease 2,3 , nephronophthisis 4 and hydrocephalus 5 . We proposed that the pleiotropic phenotype of Bardet-Biedl syndrome (BBS), which encompasses retinal degeneration, truncal obesity, renal and limb malformations and developmental delay, is due to dysfunction of basal bodies and cilia 6,7 . Here we show that individuals with BBS have partial or complete anosmia. To test whether this phenotype is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
340
0
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 342 publications
(377 citation statements)
references
References 29 publications
28
340
0
9
Order By: Relevance
“…The phenotypes of the MKKS-knockout mouse (Fath et al, 2005) closely resemble those of mice disrupted for the BBS1, BBS2, or BBS4 genes (Kulaga et al, 2004;Nishimura et al, 2004), and many of these phenotypes have been suggested to be caused by ciliary dysfunction. In the case of the BBS2-knockout mouse, the photoreceptor degeneration is preceded by mislocalization of rhodopsin, which indicates a defect in protein transport.…”
Section: Discussionmentioning
confidence: 97%
“…The phenotypes of the MKKS-knockout mouse (Fath et al, 2005) closely resemble those of mice disrupted for the BBS1, BBS2, or BBS4 genes (Kulaga et al, 2004;Nishimura et al, 2004), and many of these phenotypes have been suggested to be caused by ciliary dysfunction. In the case of the BBS2-knockout mouse, the photoreceptor degeneration is preceded by mislocalization of rhodopsin, which indicates a defect in protein transport.…”
Section: Discussionmentioning
confidence: 97%
“…Since obesity and several of the other phenotypes that accompany BBS are common, studying this disorder potentially will yield new insights into the cellular and molecular mechanisms that underlie these important phenotypes. That several of the disease phenotypes (retinal dystrophy, situs inversus, and anosmia) already were linked to cilia suggested a connection between BBS and cilia, and several recent studies have confirmed this idea [94][95][96][97] (reviewed in Mykytyn and Sheffield 98 ). The BBS1 and BBS4 gene products are essential for formation of normal cilia in mouse olfactory epithelium.…”
Section: Cilia and The Obesity Disorder Bardet-biedl Syndromementioning
confidence: 97%
“…In a study of 19 BBS patients, nine had anosmia/ hyposmia. 25 Many affected individuals suffer from a degree of clumsiness and 40% of one cohort describe signs of ataxia and poor coordination. 4 Dysdiadochokinesia and past pointing are common (79%) as are difficulties with tandem walking and the Fogg test.…”
Section: Clinical Overviewmentioning
confidence: 99%